Design a Valid and Reliable Survey for the Communication Skills Assessment of the Pharmacists and Pharmacy Students in Iran - Maryam Aghakouchakzadeh; Mandana Izadpanah; Kaveh Eslami; Ali Yadegari; Leila Kouti (Research Center for Rational Use of Drugs (RCRUD), 2018)
Background: Several essential roles defined for pharmacists which the important skills must possess in support of their roles. One of them is the essential ability, knowledge, and confident for the interactive and appropriate communication with other health professionals and the public. According to the importance of communication skills, there is a need to evaluation this ability in the pharmacist, and pharmacy students. Methods: The criteria of the communication skills assessment extracted from the "communication skills in pharmacy practice" book and the health professional educations and investigations with the focus on communication skills in pharmacy practice. Then the content validity ration (CVR) and the content validity index (CVI) were evaluated for assessing the necessity, relevancy, clarity, and simplicity. In addition, the reliability analysis was carried out for assessing of the internal consistency by the calculation of Cronbach's alpha. The data were analyzed by using the Statistical Package for Social Sciences (SPSS) version 16. Results: The finally valid and reliable survey of the communication skills assessment of the pharmacist and pharmacy students have 15 items, which include the verbal and non-verbal skills such as greeting with patients, speaking clearly, listening to what patient had to say, the professional appearance, and clear writing medication orders. Conclusion: Communication skills in pharmacy practice can be a critical ability for the development of the dealing with patients, physicians, and other health care professionals and lead to improvement of the quality health care delivery.